Penerapan Diversi Oleh Hakim Dalam Penyelesaian Perkara Pidana Anak Ditingkat Pengadilan (Studi Pengadilan Negeri Masohi) - Tetelepta, Natalisya; Latupeirissa, Julianus Edwin; Salamor, Anna Maria (PATTIMURA Law Study Review, 2024)
ABSTRACT: Diversion is the resolution of a child's case from a criminal process to a process outside of criminal law. Because children have rights to be protected, the handling of children's cases and adult cases is certainly different. Diversion can be carried out at every level, starting from investigation, investigation and even court level. With the existence of a diversion system, it is hoped that there will be legal reform in children's cases so that the diversion process is carried out to prevent children from being labeled as criminals and to prevent children from being negatively impacted by the prosecution process. Purposes of the research to find out the application of restorative justice in the diversion process in court as well as the mechanism for implementing diversion by judges in resolving criminal cases at court level. The research method in this research is normative juridical. The problem approaches used are the statutory approach, conceptual approach and case approach. The results of this research show that in carrying out the diversion process in court the judge has the right to determine which children's cases can be attempted diversion and in its implementation the judge must also seek diversion through the mechanisms that have been regulated. In children's cases with determination Number 2/Pen.Div/2023/PN Msh Jo. Number 3/Pid-Sus-Anak/2023/PN The judge has attempted diversion in accordance with the diversion implementation guidelines mechanism in PERMA No.4/2014, so that the diversion efforts carried out in the child's case at court level can be successful.